2019
DOI: 10.1088/1742-6596/1402/3/033062
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient fulfilling status for bali cows in Bali, Indonesia in season differences

Abstract: This study aims to determine the number of nutrients given in feed for Bali cows in different seasons. The study used a survey method through observations on 27 livestock groups in Bali by measuring the amount of feed given, diversity of feed ingredients, and sampling of feed ingredients for analysis. Measurements were made on three season (the rainy, mid-dry, and the peak of the dry-season). The results showed a decrease in the type and diversity of feed ingredients in the ration, while the amount of ration g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The fermentation process in processing cow dung into biological fertilizer affects the pH decrease from 8.13 to 6.77 and can eliminate pathogenic microorganisms at 50 o C [25]. Seasonal differences also affect the quality of animal feed, were in the dry season the composition of field grass in the ration increases [26], consequently, the higher the crude fiber, the higher C/N.  The same letter at the average value in the same column is not significantly different at the Duncan test level of 5%  Cow Compost (Cc), Goat Compost (Gc), Chicken Compost (Ckc), Cow Biochar (Cb), Goat Biochar (Gb), Chicken Biochar (Ckb), 0-ton ha -1 (D0), 5 ton ha -1 (D1), 10 ton ha -1 (D2), 15 ton ha -1 (D3).…”
Section: Resultsmentioning
confidence: 99%
“…The fermentation process in processing cow dung into biological fertilizer affects the pH decrease from 8.13 to 6.77 and can eliminate pathogenic microorganisms at 50 o C [25]. Seasonal differences also affect the quality of animal feed, were in the dry season the composition of field grass in the ration increases [26], consequently, the higher the crude fiber, the higher C/N.  The same letter at the average value in the same column is not significantly different at the Duncan test level of 5%  Cow Compost (Cc), Goat Compost (Gc), Chicken Compost (Ckc), Cow Biochar (Cb), Goat Biochar (Gb), Chicken Biochar (Ckb), 0-ton ha -1 (D0), 5 ton ha -1 (D1), 10 ton ha -1 (D2), 15 ton ha -1 (D3).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to obtain the quality of coffee skin waste as an animal feed ingredient, it is very necessary to carry out a fermentation process with only 2 weeks of fermentation time. When viewed from the crude protein content of fermented coffee skin waste, it is still higher than natural grass and elephant grass as the main feed for raising cattle [19] and the fulfillment of crude protein nutrient for main cattle in Bali is only 10.32 -10.41% [20]. Therefore, fermented coffee husk waste has great potential as animal feed, especially for ruminants, because: 1) the quality is quite good, 2) the availability is very large, especially in coffee-producing areas, and 3) it can reduce environmental impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a lot of coffee husk waste is wasted in coffee mills and disturbs the environment. From the results of [5] research on rice, straw fermentation using 4 types of probiotics was able to increase the protein content from 4-5% to 6-7% which was equivalent to the protein content of field grass and was able to weaken the crude fiber. For the fermentation of coffee skin waste from the results of the 2021 Matching Fund activity trial in Catur Village, the results of the increase in protein content from 8-9% to 13-15% are close to the protein content of legumes and higher than the protein content of elephant grass [4].…”
Section: 3mentioning
confidence: 99%
“…Furthermore, [4] found that fermented rice straw was able to increase crude protein content from 4-5% to 9-10%, while coffee husk waste fermentation using several types of fermenters could significantly increase crude protein content from 8-9%. to 13-20%, far exceeding the quality of field grass and elephant grass and almost the same as leguminous species [5]. Therefore, in assisting and strengthening livestock groups, it is very important to disseminate appropriate technology for the fermentation of various agricultural wastes.…”
Section: Introductionmentioning
confidence: 99%